Effect of Different Beverages and Polishing Techniques on Color Stability of CAD/CAM Composite Restorative Materials - Lassila, Lippo (United Kingdom, 2025)
Objectives: The aim of this article was to compare the colour stability of short fibre-reinforced computer-assisted design/computer-assisted manufacturing (CAD/CAM) composite (SFRC CAD) to commercially available CAD/CAM materials following prolonged immersion in a variety of beverages. Furthermore, the influence of the polishing technique was evaluated.
Materials and methods: A total of 120 rectangular specimens (10 mm length × 14 mm width × 2 mm thickness) were prepared from SFRC CAD, IPS e-max, Cerasmart 270, Celtra Duo, Enamic, and Brilliant Crios. The specimens underwent polishing through either a laboratory polishing machine equipped with 4000-grit silicon carbide paper or chairside polishing using Sof-Lex spiral. Twenty specimens of each tested CAD/CAM material were randomly divided into four groups (n = 5) based on the staining solution used in order to evaluate the colour stability of the materials. Group 1: distilled water, Group 2: coffee, Group 3: red wine, Group 4: coke. Using a spectrophotometer, the colour changes (∆E) of all CAD/CAM materials were assessed at baseline, and after 1 and 12 weeks of staining. Three-way analysis of variance was used to analyse the data (α = 0.05).
Results: The staining solution and material type showed a significant influence on the CAD/CAM specimens’ colour stability (p < 0.05), while polishing method had no significant influence (p > 0.05). The average ∆E values for specimens submerged in wine were considerably higher (p < 0.05) than those for the other solutions. SFRC CAD, Cerasmart 270, and Enamic displayed the highest ∆E values in wine (p < 0.05).
Conclusions: The colour stability of tested SFRC CAD was comparable to other composite-based CAD/CAM materials, while IPS e.max exhibited the highest level of colour stability.